The effect of the second excitation frequency mode under different conditions on the fluid streaming and microparticles acoustophoresis with the aim of separating biological cells. (February 2020) - Hosseini, Mirollah; Hasani, Mohammadamir; Biglarian, Mohit; Amoei, Amir Hossein; Toghraie, Davood; Mehrizi, Abbasali Abouei; Rostami, Sara
Highlights: Effect of the second excitation frequency mode on the fluid streaming. The resulted acoustic streaming is scrutinized. Effect of the increasing the microparticle size and aspect ratio of the microchannel increasing the microparticle size accelerates the displacement of the microparticles. Changing the aspect ratio affects the formation of the microparticle distribution. Abstract: Background and objective: In this study, the effect of the second excitation frequency mode under different conditions on the fluid streaming and its microparticles displacement is investigated. Methods: For this purpose, some variable parameters such as the particle diameter, microchannel aspect ratio, and applied frequency modes have been selected to study. The resulted acoustic streaming was scrutinized to understand the physics of the problem under different geometrical and input conditions. Finally, the effect of the increasing the microparticle size and aspect ratio of the microchannel, simultaneously, has been evaluated. Results: The results demonstrated that increasing the microparticle size accelerates the displacement of the microparticles. On the other hand, changing the aspect ratio affects the formation of the microparticle distribution and it also changes the velocity of the microparticles due to the gradient of the second-order pressure. Conclusions: The obtained results have wide applications in the military, medical, petrochemical, and other related studies.